Qualitative research as policy knowledge: Framing policy problems and transforming education from the ground up - Dumas, Michael; Anderson, Gary L. (Education Policy Analysis Archives, 2014)
As educational research becomes privatized, commodified and commercialized, research relevance increasingly means being incorporated into neoliberal ideological and economic agendas. Within this social context, qualitative research in particular is often deemed less relevant (if not irrelevant) because it does not provide prescriptions for best practices or claim to offer “proof” that a given policy will lead to specific outcomes. The authors suggest that notions of research’s relevance to policy and practice may be too narrow a way of thinking about how qualitative scholarship might enter policy discourse. Instead, they propose that scholars advance a new common sense, in which “policy knowledge” is understood as more useful—indeed, more relevant—than mere policy prescription. In their view, impacting the very framing of policy will require that scholars expand their notion of the audiences for educational research, and be more creative at reaching a diverse range of stakeholders, including not only policymakers, but also journalists, youth and community activists, and teachers.